Quality of dwarf cashew tree seedlings as a result of methods for breaking dormancy, container volume and application of bovine biofertilizer - Irineu, Toni Halan da Silva; Véras, Mário Leno Martins; Andrade, Francisco Hélio Alves de; Silva, Josimar Nogueora da; Andrade, Raimundo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The dwaf cashew tree presents enormous economic relevance for the Brazilian northeast. When establishing orchards of this species, the most important phase is the formation of the seedlings. Therefore, studies aiming to improve growth aspects and seedling qualities are extremely relevant. In this sense, the present study aimed to evaluate the growth and quality of dwarf cashew tree seedlings as a result of methods for breaking dormancy, container volume and application of bovine biofertilizer. The experiment design was completely randomized, with a 2×2×5 factorial scheme and six replicates; the experimental unit consisted of five seedlings. The treatments involved two methods of breaking dormancy (scarification with sandpaper and immersion in water), two container volumes (1 and 2 kg) and five doses of bovine biofertilizer (0, 2.5, 5.0, 7.5 and 10 mL). The method for breaking dormancy with normal water for 24 hours was the most adequate for the formation of dwarf cashew tree seedlings. The doses of 7.5 and 10 mL of bovine biofertilizer provided higher growth and quality in the dwarf cashew tree seedlings. The volume of 2 kg of substrate was the most suitable volume for growing dwarf cashew trees.